Analisis Nilai Tambah dan Keuntungan Abon Berbasis Nabati pada UMKM Abon Daun Emas di Kabupaten Sleman: Added Value and Profitability Analysis of Plant-Based Floss at UMKM Abon Daun Emas in Sleman Regency - Colbert, Steven; Permai, Ni Made Suyastiri Yani (Journal of Agricultural Social and Business, 2025)
UMKM Abon Daun Emas is a business engaged in processing plant-based food into floss products, such as banana heart floss, oyster mushroom floss, and vegetarian floss. Each product went through various processing stages with the additional inputs of raw materials, labor, and other inputs, resulting in different added values and profits. This research aimed to (1) analyze the added value of plant-based floss at UMKM Abon Daun (2) analyze the profits of plant-based floss at UMKM Abon Daun. This study used a quantitative approach with a case study method. The respondents of this research were the business owner and the production head of UMKM Abon Daun Emas, selected using purposive sampling. The data analysis technique employed descriptive analysis, added value analysis, and profit analysis using the Hayami method. The results showed that (1) oyster mushroom floss became plant-based floss with the biggest added value, which was Rp 76.848,24/Kg, while the added value of banana heart floss was Rp 59.125,48/Kg, and vegetarian floss was Rp 43.215,94/Kg. (2) Plant-based floss with the biggest profit was oyster mushroom floss which was Rp 70.598,24/Kg, while the profit of banana heart floss was Rp 53.708,81/Kg, and vegetable floss was Rp 38.549,27/Kg.